2013
DOI: 10.1017/dmp.2013.74
|View full text |Cite
|
Sign up to set email alerts
|

Community Support as a Moderator of Postdisaster Mental Health Symptoms in Urban and Nonurban Communities

Abstract: Objective We examined the association between disaster exposure, community support, and mental health outcomes in urban and nonurban participants of Galveston and Chambers counties after Hurricane Ike. The moderating effect of community support was evaluated as a protective factor relative to postdisaster mental health. Methods A representative population-based sample of 157 urban and 714 nonurban adults were interviewed 12 to 17 months after the hurricane about their mental health functioning, disaster expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 31 publications
(54 reference statements)
2
33
0
Order By: Relevance
“…This is, especially important in the context of poverty, [8, 40] structural conflict, humanitarian crisis [41] or disasters [42–45]. SC may have a significant influence on the capacity of local communities to adapt to sudden environmental events such as flooding, drought, the ongoing climate change effects [46–48] or other environmental disasters [4951]. SC can strengthen the trust between communities and local authorities, enabling better coordination of preventive and reconstructive efforts [52, 53] with social support measures [54].…”
Section: Introductionmentioning
confidence: 99%
“…This is, especially important in the context of poverty, [8, 40] structural conflict, humanitarian crisis [41] or disasters [42–45]. SC may have a significant influence on the capacity of local communities to adapt to sudden environmental events such as flooding, drought, the ongoing climate change effects [46–48] or other environmental disasters [4951]. SC can strengthen the trust between communities and local authorities, enabling better coordination of preventive and reconstructive efforts [52, 53] with social support measures [54].…”
Section: Introductionmentioning
confidence: 99%
“…As a result, potentially long-term needs, such as psychological issues, are not well addressed. Such challenges are especially problematic in rural and nonurban locations because there are typically fewer available resources (Norris, 2002; West, Price, Gros, & Ruggiero, 2013). Adolescents with post-disaster mental health difficulties are unlikely to be identified and receive treatment as a result.…”
mentioning
confidence: 99%
“…Research has demonstrated that increased perceived support from social networks (individual and a larger community) reduced the long-term effects of disaster exposure on mental health in a sample of hurricane survivors. 14 Similarly, increased social support can be associated with reduced symptoms of posttraumatic stress disorder (PTSD), depression, and generalized anxiety disorder in adults who were exposed to Hurricane Andrew. Social support also was found to be related to measures of general distress in a sample of individuals exposed to Hurricane Katrina.…”
Section: Discussionmentioning
confidence: 99%